Sulfonated poly(ether ether ketone)/sulfonated graphene oxide hybrid membrane for vanadium redox flow battery. (20th August 2018) - Zheng, Lanyue; Wang, Haixia; Niu, Ruiting; Zhang, Yuxia; Shi, Haifeng
Abstract: In this paper, a series of sulfonated poly(ether ether ketone) (SPEEK) hybrid membrane doped by the different amount of sulfonated graphene oxide (SGO) nanosheets are prepared by solution-casting method. The membrane structure, physicochemical property and cell performance of vanadium redox flow battery (VRB) have been characterized through FT-IR, SEM, XPS, and single-cell test system, etc . The incorporation of SGO in SPEEK improves the water uptake, ion exchange capacity and proton conductivity of the hybrid membrane, and effectively reduces the swelling degree and the vanadium ion permeability. In the single cell performance test, the energy efficiency of the SPEEK/SGO-3 hybrid membrane is 81.1%, which is higher than that of SPEEK (76.0%) and Nafion 117 membrane (73.8%). And, a longer self-discharge time (56.6 h) against Nafion 117 (23.5 h) and SPEEK (32.8 h) membrane is shown. In addition, the incorporated SGO nanofillers don't improve the chemical stability of SPEEK membrane soaked by 1.5 M V 5+ solution although they block the vanadium ion permeation. Then, the durability for SPEEK/SGO hybrid membranes should be further explored for VRB system.